Ovarian characteristics, serum concentrations, and fertility in lactating dairy cows in response to equine chorionic gonadotropin - Pulley, Stephanie Leeann (Kansas State University, 2011)
The objectives were to evaluate the effects of equine chorionic gonadotropin (eCG) administration on preovulatory follicle diameter, serum estradiol and progesterone concentration, corpus luteum (CL) diameter, estrual activity, and pregnancy rate. Lactating dairy cows were submitted to a Presynch-Ovsynch timed artificial insemination (TAI) protocol. Cows (n = 121) in a single herd were treated with 2 injections of prostaglandin F2α (PGF) 14 d apart (Presynch), with the second injection administered 11 d before the onset of a timed AI protocol (Ovsynch; injection of GnRH 7 d before and 56 h after PGF2α, with TAI administered 16 to 18 h after the second GnRH injection). Cows were assigned randomly to receive either saline or 400 IU eCG concurrent with the PGF2α injection of the Ovsynch protocol (d 0). Blood samples were collected during the study to monitor serum changes in progesterone and estradiol to determine if eCG would facilitate increased estrual activity, improved ovulatory response to GnRH, and enhanced post-ovulatory luteal function. Administration of eCG tended to increase the number of CL and on d 9 and 16 after PGF2α, corresponding to d 6 and 13 post-ovulation. Volume of the post-eCG treatment luteal tissue was increased only on d 16. Timed AI pregnancy rates did not differ between eCG (36.9%) and control cows (41.8%). We concluded that use of eCG provided no profertility advantages to dairy cattle when programmed for a timed insemination at first service.
Keywords: eCG; Fertility; Ovsynch; Animal Sciences (0475)